Localized Near Surface Temperature Inversion Forecasting Using Long Short-Term Memory - Dinkins, Taylor; Wong, Weng-Keen; Amogi, Basavaraj; Pesantez-Cabrera, Paola; Patel, Jaitun; Khot, Lav; Fern, Alan (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Near surface temperature inversions are periods in which a low layer of warm air is trapped between cooler air higher up in the atmosphere and dense cooler air below it near the surface level. By causing cooler air to pool near the surface level, inversions can have detrimental effects for crop growers, including frost, increased moisture, and pesticide drift. As a result, predicting the occurrence and magnitude of these inversions yields substantial benefits for growers. We introduce a Long Short-Term Memory (LSTM) model for temperature inversion forecasting that is able to effectively predict localized, near surface temperature inversions in advance such that growers can take actions to mitigate the detrimental effects. We show a substantial performance gain over a deployed temperature inversion forecasting system, and include a series of ablations that show the benefit of using publicly available terrain-specific feature information when modeling inversions at this scale.